Women in Policing and Legitimacy: A Vignette-Based Study of Symbolic Representation - Schuck, Amie M. (Women & criminal justice, 2021)
Using a two-by-two vignette-based experimental design, this study aimed to examine the effects of women’s symbolic representation in sexual assault units and the arrest rate for interpersonal violence cases on individuals’ perceptions of police legitimacy, support for leadership, and willingness to engage in bystander intervention behaviors. Using responses from 357 students attending one university in the Midwest, the results showed that a higher level of women’s representation was associated with more police legitimacy and greater support for the leader when the agency had a low arrest rate. Whereas police legitimacy was related to bystanders’ intentions to intervene, women’s representation in the unit and the arrest rate was not. The findings indicate that women’s representation in policing strengthens the support for the police in gendered areas when the agency is underperforming.